Obstructed DC glow discharge in low-pressure nitrogen - Lisovskiy, V.; Kravchenko, E.; Skubenko, E.; Kharchenko, N.; Yegorenkov, V. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
We studied in experiment the obstructed and abnormal modes of dc glow discharge in nitrogen as well as the transition between them. It is shown that the obstructed discharge may exist only in the gas pressure range p < 0.2 Torr under conditions corresponding to the left-hand branch of Paschen curve. The dc glow discharge was shown to possess an S−shaped current-voltage characteristic. The transition from the obstructed mode to the abnormal is shown to be accompanied by LF relaxation oscillations of the discharge current in a kilohertz range.